Influence of the geographic distribution of prion protein gene sequence variation on patterns of chronic wasting disease spread in white-tailed deer (Odocoileus virginianus). Issue 3 (4th July 2018) - Brandt, Adam L.; Green, Michelle L.; Ishida, Yasuko; Roca, Alfred L.; Novakofski, Jan; Mateus-Pinilla, Nohra E.
ABSTRACT: Managing and controlling the spread of diseases in wild animal populations is challenging, especially for social and mobile species. Effective management benefits from information about disease susceptibility, allowing limited resources to be focused on areas or populations with a higher risk of infection. Chronic wasting disease (CWD), a transmissible spongiform encephalopathy that affects cervids, was detected in Colorado in the late 1960s. CWD was detected in Illinois and Wisconsin in 2002 and has since spread through many counties. Specific nucleotide variations in the prion protein gene ( PRNP ) sequence have been associated with reduced susceptibility to CWD in white-tailed deer. Though genetic resistance is incomplete, the frequency of deer possessing these mutations in a population is an important factor in disease spread (i.e. herd immunity). In this study we sequenced 625 bp of the PRNP gene from a sampling of 2433 deer from Illinois and Wisconsin. In north-central Illinois where CWD was first detected, counties had a low frequency of protective haplotypes (frequency <0.20); whereas in northwestern Illinois counties, where CWD cases have only more recently been detected, the frequency of protective haplotypes (frequency >0.30) was much higher ( p  < 0.05). Protective haplotype frequencies varied significantly among infected and uninfected geographic areas. The frequency of protective PRNP haplotypes may contribute to population level susceptibility and may shape the way CWD has spread through Illinois. Analysis of PRNP haplotype distribution could be a useful tool to assess CWD risk and allocate resources to contain and reduce the spread of infection.